The Simulation of Land Use Change On Soil Erosion and Sediment Transported Using SWAT Hidrological Models In The Upstream of Mrica Reservoir Catchment Area - Lukman Hidayat; Bambang Sulistyo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2019)
The phenomenon of land conversion of natural forest into agricultural cultivation is an event in nature that must be understood to determine action in the future. The aim of this research was to know the influence of land use changes to soil erosion and sediment transported. Simulation on hydrological model was used as research method. Soil Water Assessment Tool (SWAT) Hydrological models that have been validated on a very good level based on the Nash-Sutcliffe Efficiency (NSE), is used to simulate in land use changes, based on Land Cover Index Changes (IPL) permanent and production scenarios, on soil erosion (SYLD) and sediment transported (Sed-out), in 101,027.250 hectares of the upstream of Mrica reservoir catchment area. SWAT model simulation results indicate that quantitatively, the increase IPL permanent followed by a decrease in IPL production has the potential to lower the value of soil erosion ton/hectares/year) of approximately 5.77% to 82.37% and from 5.15% to 75.12% of sedimentary transported (mm/year). Qualitatively, positive Extreme scenario, can increase the value of soil erosion in some sub-catchments and the upstream of Mrica reservoir catchment area, from worse quality on the existing condition become moderate, and even good. Watershed management efforts to reduce the rate of soil erosion and sediment transported on the river, with land use changes should be followed by soil and water conservation techniques such as bench terraces and contouring.